Biocomputing 2000 1999
DOI: 10.1142/9789814447331_0002
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Evolution Explained (Sort Of)

Abstract: Sites in proteins evolve at markedly different rates; some are highly conserved, others change rapidly. We have developed a maximum likelihood method to identify regions of a protein that evolve rapidly or slowly relative to the remaining structure. We also show that solvent accessibility and distance from the catalytic site are major determinants of evolutionary rate in eubacterial isocitrate dehydrogenases. These two variables account for most of the rate heterogeneity not ascribable to stochastic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Beginning graduate students studying a novel protein learn that to knock out function, the best places to mutate the protein are the most conserved sites. This relationship is sometimes viewed as almost a tautology, so conserved sites are believed to be functionally important by definition, but surveys of many proteins have revealed that residue conservation can be well predicted based on a combination of distance from active sites and distance from the hydrophobic core (Dean and Golding, 2000). An important development based on this relationship has been that changes in residue conservation can be viewed (again, sometimes tautologically) as strong predictors of changes in the function of those residues.…”
Section: Introductionmentioning
confidence: 99%
“…Beginning graduate students studying a novel protein learn that to knock out function, the best places to mutate the protein are the most conserved sites. This relationship is sometimes viewed as almost a tautology, so conserved sites are believed to be functionally important by definition, but surveys of many proteins have revealed that residue conservation can be well predicted based on a combination of distance from active sites and distance from the hydrophobic core (Dean and Golding, 2000). An important development based on this relationship has been that changes in residue conservation can be viewed (again, sometimes tautologically) as strong predictors of changes in the function of those residues.…”
Section: Introductionmentioning
confidence: 99%
“…Others have also described catalytic residues and their local environment as highly conserved (Zvelebil et al 1987;Dean and Golding 2000;Bartlett et al 2002). The concept of an "environment" that we analogize with our ∼30 Å diameter most-conserved Zone 9 was suggested by reports indicating that more effective functional change (enantioselectivity, substrate specificity, new catalytic activity) are associated with amino acid substitution close to catalytic sites.…”
Section: Discussionmentioning
confidence: 81%
“…ESF analyses estimate rates within a window, normalize the local rates by the average rate, smooth the rates to detect ECRs, and then rank the ECRs by the rate of the most slowly evolving window. This combination of algorithms distinguishes the method from similar approaches that either require structures (7,8), do not predict or rank ECRs, or separately estimate rates for each position (9). One key assumption we make is that of a strong correlation of rates in sites that are close in the alignment.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6]. A more recent application of estimating rate variation within proteins has been the inference of structural and functional constraints (7)(8)(9).…”
mentioning
confidence: 99%